2021
DOI: 10.1101/2021.12.13.21267725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vaccine breakthrough and the invasion dynamics of SARS-CoV-2 variants

Abstract: Vaccination provides a powerful tool for mitigating and controlling the COVID-19 pandemic. However, a number of factors reduce these potential benefits. The first problem arises from heterogeneities in vaccine supply and uptake: from global inequities in vaccine distribution, to local variations in uptake derived from vaccine hesitancy. The second complexity is biological: though several COVID-19 vaccines offer substantial protection against infection and disease, 'breakthrough' reinfection of vaccinees (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…With simple mathematical models of immuno-epidemiological dynamics, we showed that the medium- and long-term population-level landscapes of immunity and infection crucially depend on the strength and duration of immunity following infection or vaccination [8]. We also explored the intricacies that emerge from vaccine dosing regimes (for two-dose vaccines) [10] or from the invasion dynamics in largely vaccinated populations [12], in addition to the consequences of vaccine nationalism [11]. Throughout, we have shown how epidemiological and/or evolutionary outcomes hinge on the characteristics of host immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…With simple mathematical models of immuno-epidemiological dynamics, we showed that the medium- and long-term population-level landscapes of immunity and infection crucially depend on the strength and duration of immunity following infection or vaccination [8]. We also explored the intricacies that emerge from vaccine dosing regimes (for two-dose vaccines) [10] or from the invasion dynamics in largely vaccinated populations [12], in addition to the consequences of vaccine nationalism [11]. Throughout, we have shown how epidemiological and/or evolutionary outcomes hinge on the characteristics of host immune responses.…”
Section: Introductionmentioning
confidence: 99%